Anticholinergic Drug Use on Admission and the Risk of In-Hospital Falls in Older Hospitalized Patients - Akgün Ö; Oudshoorn C; Mattace-Raso FUS; Egberts A (Clinical Interventions in Aging, 2022)
Özge Akgün,1 Christian Oudshoorn,1 Francesco US Mattace-Raso,1 Angelique Egberts1,2 1Department of Internal Medicine, Section of Geriatric Medicine, Erasmus MC University Medical Center, Rotterdam, the Netherlands; 2Department of Hospital Pharmacy, Franciscus Gasthuis & Vlietland, Rotterdam & Schiedam, the NetherlandsCorrespondence: Angelique Egberts, Section of Geriatric Medicine, Department of Internal Medicine, Erasmus MC University Medical Center, Room Rg-527, PO Box 2040, Rotterdam, CA, 3000, the Netherlands, Tel +31 10 70 35979, Fax +31 10 70 34768, Email a.egberts@erasmusmc.nlPurpose: In-hospital falls, especially among older patients, are a major and underestimated problem. Several studies have suggested a possible association between anticholinergic drug use and falls, but the results are inconclusive and studies focusing on in-hospital falls are scarce. The aim of the present study was to investigate whether anticholinergic drug exposure on admission is associated with in-hospital falls.Patients and Methods: This retrospective chart review study was conducted in the Erasmus MC University Medical Center, Rotterdam, the Netherlands. Patients aged 65 years and older, who were acutely admitted to the geriatric ward between 2012 and 2015, were included. Anticholinergic drug exposure was determined with the Anticholinergic Risk Scale (ARS), the Anticholinergic Cognitive Burden scale (ACB) and the list of Chew. Logistic regression was used to investigate the possible association between anticholinergic drug exposure and in-hospital falls. Analyses were adjusted for age, sex, fall history, fall as reason for admission, number of drugs on admission, use of a mobility aid and delirium.Results: A total of 905 patients were included, of which 94 patients experienced one or more in-hospital falls. Each additional anticholinergic drug in use, according to the ARS, was associated with an increased odd of experiencing a fall (OR = 1.49, 95% CI: 1.06– 2.10). Other measures, ie anticholinergic drug use (yes/no) and different categories of anticholinergic drug burden, measured with the ARS, ACB and list of Chew, were all not associated with in-hospital falls.Conclusion: Anticholinergic drug exposure on admission is possibly not a main risk factor for in-hospital falls among older patients.Keywords: accidental falls, cholinergic antagonists, inpatients